Morphological characterization of karyotype for Guadua angustifolia Kunth Var. angustifolia. (Bambusoide: Poaceae) (Revista de Investigaciones Universidad del Quindío, 2012)
Guadua angustifolia has economic and ecological importance in the regions where it is native and in those where it has been introduced. In the present study was to study morphology chromosome from root meristem tissue. The results showed that the chromosome number is equal to 2n=2X= 46, with X= 23. This is the first cytogenetic report for the specie. Morphological characterization of chromosomes allowed us to establish the presence of 4 categories metacentric chromosome being the most frequent (39% of the karyotype). It is proposed to classify the chromosomes according to size in 5 categories ranging for 0,6 to 1,5um long. These observations are consistent with previous reports on the karyotype of the species, which is considered as a functional diploid.
Keywords: cytogenetic; Karyotipification; Chromosome; Asymmetry index